Validated tools used to assess musculoskeletal injuries in dancers: A systematic review - Panosso, I.; Senger, D.; dos Santos Delabary, M.; Angioi, M.; Haas, A. N. (Journal of Dance Medicine & Science, 2024)
Introduction: Dance is a physically demanding art form that often results in musculoskeletal injuries. To effectively treat these injuries, standardized and reliable assessment tools designed to the dancer`s needs are required. Thus, the aim of this review is to identify studies that have employed validated tools to assess musculoskeletal injuries in ballet, modern, and contemporary dancers, focusing on describing the content and psychometric quality of the tools used.